Artificial Intelligence (AI) and Automation in the World of Work: A Threat to Employees? - Mabungela, Mvuyisi (Research in Social Sciences and Technology- OpenED Network, 2023)
The introduction of machines driven by artificial intelligence (AI) and automation technologies has already had a significant impact on the manufacturing, automotive, logistics, retail, and wholesale industries, and the repercussions of their replacement on the human labour has been a hotly disputed subject. AI and automation technical advancements are having a big influence on workforce turnover. The aim of this study was to look at employees' attitudes on Artificial Intelligence and Automation at work, specifically whether they see AI as a threat or not. Secondary data sources from several authors were utilised in this article. This data was gathered from published and peer-reviewed publications, internet sources, and textbooks pertinent to the issue under consideration. Some researchers contend that automation is likely to add to South Africa's high unemployment rate. There is a scarcity of empirical data in the form of published empirical research concentrating on the stress that AI and automation place on employees, hence the study is being conducted. Based on this study, it appeared that employees feel threatened by this rise of Artificial Intelligence and Automation.